Nutritional Composition, Physicochemical, and Sensory Properties of Snack Bars Produced from Catfish Head Powder (Clarias gariepinus) and Purple Sweet Potatoes (Ipomoea batatas var Ayumurasaki) as Emergency Food - Canti, Meda; Kasanti, Nafera Arvianda; Hutagalung, Rory Anthony; Lukas; Pandjaitan, M. M. Lanny W. (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research 1. The development of snack bars from catfish head powder (CHP). 2. The CHP was rich in nutritional composition and could be an additive ingredient in snack bars. 3. Adding CHP increased protein, lipid, and fibre content in the snack bars. 4. Snack bars with the addition of CHP were acceptable on all sensory attributes. 5. Snack bars produced from CHP could be used as an alternative emergency food. Abstract During natural disasters, emergency food is often needed to meet the victims’ nutritional intake such as protein, fat, carbohydrates, and energy. As an alternative, catfish heads, which are usually rich in nutritional content, can be developed into a snack bar product as emergency food. This research aimed to evaluate the chemical, physical and sensory properties of snack bars produced from catfish head powder (CHP) and purple sweet potato flour (PSPF). This research consisted of several stages, namely making CHP and PSPF, preparing snack bars, and analysing snack bars’ chemical, physical, and sensory properties. The ratios of CHP and PSPF in the preparation of snack bars stage were F0 (0:100), F1 (25:75), F2 (50:50), and F3 (75:25). The CHP contained 43.52% protein, 21.24% lipid, 4.6% fiber, and 384.38 Kcal/100 g total energy. The addition of CHP and PSPF affected the chemical (proximate and antioxidant activity), physical (redness and hardness values), and sensory (aroma and overall acceptance) properties of the produced snack bars. All snack bars had protein content that complied with Indonesian National Standards (INS) for cereal bar biscuits. The protein, lipid, carbohydrate, and total energy content of the snack bar were in accord with the standards of the United States Department of Agriculture (USDA), Food Standards Australia New Zealand (FSANZ), and emergency food standards. It is also revealed that F2 was the best treatment based on its chemical, physical, and sensory properties. Indeed, snack bars from CHP and PSPF can be utilized as an emergency food alternative.